Importance of including agronomic and climatic (abiotic) traits for reaching National Rice Development Strategy targets by 2030 in Kenya - Connor, Melanie (CGIAR, 2024)
This review aims to inform discussions on opportunities for rice breeding to respond to agronomic challenges that are pertinent in sub-Saharan Africa, especially in Kenya, as well as the changing climatic conditions in Kenya’s various ecosystems. Using a narrative review approach, journals, periodicals, reports, and government publications from diverse sources were reviewed. The online platform GloMIP provided access to the CGIAR Seed Product Market Segment (SPMS) Database and the target product profiles (TPPs) associated with these segments. It was also used to assess possible impact opportunities for improving (1) climate adaptation and mitigation; (2) environmental health and biodiversity; (3) gender equality, youth, and social inclusion; (4) nutrition, health, and food security; and (5) poverty reduction, livelihoods, and jobs. Impact opportunities were calculated for all rice market segments across the CGIAR impact areas. Results show that the breeding pipelines MELS-I and ELS-R have the greatest potential for impact in Eastern Africa and, potentially, Kenya. The corresponding TPPs need to be reassessed to improve agronomic and abiotic traits that are currently not represented—for example, the inclusion of nutrient-use efficiency or water-use efficiency. Market segmentation in Kenya also needs to be reassessed since market segments capture only half of the current rice growing area. A potential unrecognized market segment exists due to rice-based intercropping systems in western Kenya, suggesting an intercropping production system, for example, with common beans.